Electrical System Design for a Telecommunication Tower at Site Mdn302 Mabar Gudang, Medan City - Wahyu Pranata; Dino Erivianto; Parlin Siagian (Sean Institute, 2026)
This study discusses the analysis of the electrical system at the MDN302 Mabar Gudang Site, which is used to support the operation of telecommunications equipment. The electricity supply at the site comes from a three-phase PLN network with a voltage of 380/220 V, but the installed operational loads use a single-phase system (phase–neutral). The study was conducted through field surveys, electrical parameter measurements, and technical calculation analysis to evaluate the performance of the electrical distribution system. The analysis includes power calculations, system current, distribution cable voltage drop, MCB capacity selection, and evaluation of the grounding and lightning protection systems. Voltage drop calculations were performed using a single-phase system approach with copper conductors and international units (SI). The calculation results show that the voltage drop value on all distribution lines is below the maximum limit of 5% according to the 2011 PUIL standard. The grounding resistance value obtained of 0.5 Ω also indicates that the grounding system has met safety requirements. In addition to technical aspects, this study also presents a Bill of Quantities (BoQ) as part of the electrical system material planning. The selection of MCB capacity and relatively large cable sizes was carried out as a long-term planning strategy to anticipate future load increases. Based on the analysis results, the electrical system at Site MDN302 Mabar Gudang was declared safe, reliable, and feasible for operation.